The topical issues of symptoms and diagnosis of cutaneous tuberculosis - N. N. Parpieva; N. S. Saipova; D. B. Rakhimov; F. B. Miradilova (Туберкулез и болезни лёгких)
The article presents data from 48 publications about clinical signs and diagnostics of cutaneous tuberculosis.